'Z-DNA like' fragments in RNA: a recurring structural motif with implications for folding, RNA/protein recognition and immune response. Issue 12 (5th May 2016) - D'Ascenzo, Luigi; Leonarski, Filip; Vicens, Quentin; Auffinger, Pascal
Abstract: Since the work of Alexander Rich, who solved the first Z-DNA crystal structure, we have known that d(CpG) steps can adopt a particular structure that leads to forming left-handed helices. However, it is still largely unrecognized that other sequences can adopt 'left-handed' conformations in DNA and RNA, in double as well as single stranded contexts. These 'Z-like' steps involve the coexistence of several rare structural features: a C2'-endo puckering, a syn nucleotide and a lone pair–π stacking between a ribose O4' atom and a nucleobase. This particular arrangement induces a conformational stress in the RNA backbone, which limits the occurrence of Z-like steps to ≈0.1% of all dinucleotide steps in the PDB. Here, we report over 600 instances of Z-like steps, which are located within r(UNCG) tetraloops but also in small and large RNAs including riboswitches, ribozymes and ribosomes. Given their complexity, Z-like steps are probably associated with slow folding kinetics and once formed could lock a fold through the formation of unique long-range contacts. Proteins involved in immunologic response also specifically recognize/induce these peculiar folds. Thus, characterizing the conformational features of these motifs could be a key to understanding the immune response at a structural level.